Tindak Tutur Ilokusi dalam Film Animasi Salahuddin Al-Ayyubi - Erip Primadani (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
This article discusses speech acts in the animated film Salahuddin al-Ayyubi. This research method is descriptive qualitative. By using the method of listening and recording the data in the form of words and sentences in this film were collected and analyzed. The formal object as a scalpel in this research is pragmatics, namely the theory of illocutionary speech acts. The results showed that in the film Salahudduin al-Ayyubi episode 1 there were 37 illocutionary speech acts. Judging from the type, of the 37 illocutionary speech acts, there are 4 types of illocutionary acts consisting of 22 directive illocutionary speech acts, 6 assertive illocutions, 7 commissive illocutions and 8 expressive illocutions. Judging from the literal and direct illocutionary speech acts, of the 37 illocutionary speech acts there are 15 literal and direct speech acts, 1 indirect and literal speech act, 9 literal and indirect speech acts, and 12 non-literal and indirect speech acts.